(untitled) (Development Service Industry Management, 2025)
The relevance of this research is determined by the growing role of corporate culture in today’s dynamic business environment, where it evolves from a set of formal norms, rules, and traditions into a strategic resource for enterprise development. Modern corporate culture not only ensures team cohesion and employees’ commitment to shared values but also serves as a crucial factor of adaptation to market changes, strengthening competitiveness, and stimulating innovation. Therefore, the study of mechanisms for its formation and maintenance acquires particular scientific and practical significance. Despite the considerable attention given to this issue in academic literature, many aspects of corporate culture development remain insufficiently studied. In particular, the challenges of embedding corporate values into daily business practices, establishing effective internal communication, and preserving cultural integrity during crises or transformational changes are still unresolved. The works of leading scholars such as E. Schein, G. Hofstede, and D. Denison highlight the key components of organizational culture – values, norms, and behavioral patterns – and propose approaches to its measurement and development. However, most of these concepts are tailored to large corporations and do not fully account for the specific conditions of small and medium-sized enterprises in emerging markets, including Ukraine, thus creating space for further research. The purpose of this study is to theoretically substantiate corporate culture as a strategic resource for sustainable enterprise development. It is shown that corporate culture builds trust and cooperation, ensures the consistency of managerial decisions, strengthens the achievement of strategic goals, and serves as a foundation for long-term organizational resilience. Its formation is conceptualized as a phased process that includes the identification of core values, the establishment of norms and traditions, the development of internal communication, and the integration of culture into strategic management systems. The study concludes that corporate culture represents an integrative platform for achieving sustainable growth, adaptability to external changes, and the creation of long-term competitive advantages. It should be understood not only as a managerial tool but also as a strategic resource that defines the future of the enterprise and its positioning in the global competitive environment.